Hidden Tales of Ebola: Airing the Forgotten Voices of Ugandan “Ebola Nurses” - Wonyima, Isaac Okello; Kerry, Susan Fowler; Nambozi, Grace; Barry, Charlotte; Wills, Jeanie; Clarke, Yolanda Palmer; Locsin, Rozzano C. (Journal of Transcultural Nursing, 2021)
Introduction: According to the Centers for Disease Control and Prevention, Ebola has affected the lives of thousands, including health care workers. With few studies describing the experience of nurses who survived Ebola, the study aimed to describe Ugandan nurses’ experiences. Method: Using a phenomenological design, in-depth interviews were conducted among five Ugandan nurses who contracted Ebola and survived. Result: Thematic analysis revealed themes of expectations of dying, hopelessness, loneliness, and betrayal by family, community, and the health system. Discussion: Results support the need for policies targeting holistic practice protocols to protect all health care professionals during future outbreaks. Last, nursing survivors should have access to government-guaranteed support programs, including free health care and financial stipends. These results and recommendations transcend to the current reality of living with COVID-19 (coronavirus disease 2019). Efficient practice protocols could protect all rights and privileges and contribute to access to treatment and stigma removal.
Keywords: nursing practice; transcultural health; women’s health; phenomenology; Ebola